2016
DOI: 10.1038/srep38096
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome scanning for the litter size trait associated genes and SNPs under selection in dairy goat (Capra hircus)

Abstract: Dairy goats are one of the most utilized domesticated animals in China. Here, we selected extreme populations based on differential fecundity in two Laoshan dairy goat populations. Utilizing deep sequencing we have generated 68.7 and 57.8 giga base of sequencing data, and identified 12,458,711 and 12,423,128 SNPs in the low fecundity and high fecundity groups, respectively. Following selective sweep analyses, a number of loci and candidate genes in the two populations were scanned independently. The reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 32 publications
2
71
0
Order By: Relevance
“…) and fecundity ( SETDB2 ) (Lai et al . ) traits and in maternal behavior ( ADRA2B ) (Michenet et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…) and fecundity ( SETDB2 ) (Lai et al . ) traits and in maternal behavior ( ADRA2B ) (Michenet et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study conducted by Lai et al (2016) reported the genes controlling the fecundity in dairy goat, which include gonadotropins, ovarian steroid hormones, luteinizing hormones, follicle-stimulating hormone, 17β-estradiol (E2), progesterone, activin A, etc. [9]. Earlier studies have also reported that inactive homozygous mutations in transforming growth factor β, BMP15, and GDF9 superfamily genes leads to decreased ovulation rates which further leads to sterility in dairy goat [10,11] (Supplementary Information-S1).…”
Section: Resultsmentioning
confidence: 95%
“…SMAD2 plays an essential role in regulating chondrocyte proliferation and differentiation in the growth plate (Wang W. et al, 2016). Additionally, SMAD2 was identified as the causative gene for the body-size of dogs, and was associated with the total number of piglets born in Yorkshire pigs as well as with high fecundity in dairy goats (Rimbault et al, 2013;Lai et al, 2016;Wang et al, 2018). Our results suggest that causative variants in this intergenic region may contribute to birth weight phenotypes by interfering with the regulatory function of the nearby distal regulatory elements and causing differential expression of the two surrounding genes.…”
Section: Discussionmentioning
confidence: 99%